PELATIHAN PEMBUATAN VIRGIN COCONUT OIL DI DESA MAMALA, KECAMATAN LEIHITU, KABUPATEN MALUKU TENGAH - Sipahelut, Sophia Grace (Universitas Pattimura, 2023)
Coconut is a plantation commodity with abundant potential in Mamala Village, Leihitu District, Central Maluku Regency. However, the use of coconut is still very minimal, where people only use it as a food supplement, even though coconut meat has important nutritional content when processed into Virgin Coconut Oil (VCO) products. VCO is becoming a trend among the public because it has good benefits for the health of the body and is easy to process. The purpose of this activity is to increase the knowledge and skills of the community in processing coconut meat into VCO. The target of this activity is a group of mothers in Mamala Village, Leihitu District, Central Maluku Regency. The method used is counseling and training activities. Through counseling activities carried out, it can provide knowledge to the Mamala Village community about the potential of coconut and its nutritional content, VCO and its benefits, as well as the technology for processing coconut into VCO. Training activities provide new skills to the people of Mamala Village regarding VCO processing techniques. This service activity received a positive response from the participants and provided benefits for the participants who attended. The results of the evaluation showed that after the counseling and training activities on VCO processing were carried out, the knowledge and skills of the participants increased by 90-95%.